Organizational enablers for project governance and governmentality in project-based organizations. Issue 4 (May 2015) - Müller, Ralf; Pemsel, Sofia; Shao, Jingting
Abstract: This study identifies organizational enablers (OEs) for governance and governmentality in the realm of projects in project-based organizations (PBOs). We use a multiple case study design with six firms in Sweden and China to identify OEs. Institutional theory serves as theoretical perspective. Results show that OEs are interwoven, albeit with different strength, with the three pillars of institutional theory (regulative, normative and cultural–cognitive). OEs for project governance and governance of projects fall predominantly into the category of regulative and normative pillars, whereas OEs for governmentality belong mainly to the cultural–cognitive pillar. Collectively these OEs provide for an ambidexterity of flexibility and stability, which allows organizations to align their internal characteristics with their organizational context. Managerial and theoretical implications of the results are discussed. Highlights: Organizational enablers for project governance, governance of projects, and governmentality Enablers categorized by regulative, normative and cultural–cognitive Collectively enablers provide for flexibility, stability and alignment.